THE EFFECTS OF SELF-EFFICACY ON LEARNERS’ PERCEPTIONS OF COGNITIVE PRESENCE IN ONLINE COLLABORATIVE LEARNING ACTIVITIES - Wang, Chang Hwa; Shan, Siqi (PEOPLE: International Journal of Social Sciences, 2018)
The applications of web2.0 platforms provide online learning opportunities to focus more on community collaborations as well as the knowledge construction. Cognitive presence (CP) is one of the most critical elements of community of inquiry, and ideal learning outcomes would require deeper stages of cognitive presence (integration and resolution stages), that usually difficult to achieve. Past research on CP felt short in investigating the influences of individual differences, including the effects of learners’ internal motivation on higher-order thinking. We consider Self-efficacy is one of such as it emphasizes a combination of learners’ motivation and cognition. This study intends to explore the influence of learners’ online learning self-efficacy on CP, as well as to explore the relationship between learners’ CP and learning achievements.An experiment was conducted to verify the above issues. Participants were 8th graders from a vocational school. They were required to complete their learning tasks through online collaboration by Facebook and Google Cloud. Questionnaires were applied to measure learners’ CP and self-efficacy after study. Results show that phase’s distribution of learners’ CP in this study is satisfying, and there are significant correlations between CP and self-efficacy as well as CP and learning achievements. Therefore, this study suggests that instructors should take different strategies for students with different self-efficacy and take some strategies which can enhance self-efficacy.